Remembered words : essays on genre, realism, and emblems - Fowler, Alastair (Oxford, United Kingdom : Oxford University Press, 2021)
Remembered Words is a selection of Alastair Fowler's essays on genre, realism, and the emblem (three interrelated subjects), published over six decades. It offers readers a way to arrive at a sense of how approaches to these subjects have changed over that period. Specifically, it shows how genre has come to be understood in terms of family resemblance theory. Remembered Words argues that realism can be seen as altering historically, so that Renaissance realism, for example, differs from those of later periods. Similar changes are traced in the emblem, which Fowler shows to be not only a particular genre, but an element of various kinds of realism. Famous passages in ancient literature are remembered in the familiar emblems of the Renaissance; and Renaissance0emblems form the basis of metaphors in later literature. 0Meanwhile, the general approach of the critic and the reader has been altering over the years-as becomes evident when one takes into account the time-scale of sixty years (an unusually long working life for a critic). Modern theoretical approaches-which are often casually regarded as self-evident-may appear less inevitable and more arbitrary. This is not to say that they are necessarily wrong, just that they need to be argued for. Remembered Words is intended for senior undergraduates and for graduate students, who may use it to form ideas of Fowler's approach and that of his contemporaries and predecessors over the last half century.
Includes bibliographical references (pages [271]-274) and index.
Keywords: Literature -- History and criticism; Criticism; Criticism; Literature; Criticism, interpretation, etc